PENGARUH SISTEM PENGENDALIAN INTERNAL, PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPETENSI APARATUR TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI KASUS DI KECAMATAN SINE KABUPATEN NGAWI) - Zulaikah, Apriyani; Suharno, Suharno; Widarno, Bambang (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This research was conducted on village officials in Sine District, NgawiRegency. The population in this study were all parties involved in the preparationof the APBDes in Sine District, Ngawi Regency, totaling 150 people. Thesampling technique in this study used a non-probability with a purposivesampling method. The data collection technique is done by using a questionnairemethod. The results of this study indicate that the internal control system, the useof information technology and the competence of the apparatus have a significantpositive effect on the accountability of village fund management in Sine District,Ngawi Regency.